Exploring the Fusion of Enterprise Architecture, Blockchain, and AI in Digital Governance: A Systematic Review - Hakimi, Musawer; Zarinkhail, Mohammad Shuaib; Musawi, Sayed Zabihullah (International Journal Software Engineering and Computer Science (IJSECS), 2024)
The worldwide significance of the digital revolution in governance has grown recently, with governments using cutting-edge technology to enhance services, transparency, and citizen engagement. The research investigates the integration of blockchain technology, artificial intelligence (AI), and enterprise architecture (EA) into digital governance. Examining how these technologies may enhance government services' effectiveness, responsibility, and openness might contribute to a deeper understanding of them. Encompasses all literary works published between 2017 and 2024, including scholarly articles, conference papers, and reputable reports from repositories such as Google Scholars, IEEE Xplore, Scopus, Web of Science, and SpringerLink. This comprehensive analysis examines the functions of artificial intelligence (AI), blockchain technology, and enterprise architecture (EA) in electronic government (e-government) initiatives. An extensive dataset uncovers prevalent concerns, challenges, opportunities, and effects across several technologies. The research findings indicate that the EA framework significantly enhances interoperability and efficiency. Additionally, blockchain technology guarantees data integrity and transparency by using immutable records. Moreover, artificial intelligence enhances service delivery by automating procedures and improving decision-making skills. Nevertheless, the process of incorporating these technologies may need some help. These challenges include the compatibility between blockchain and existing systems, the need for skilled workers in AI, and reluctance to change inside organizations. Although there are some problems, it may provide advantages such as less duplication of tasks, enhanced traceability, and heightened public confidence. Integrating blockchain, artificial intelligence, and enterprise architecture presents unparalleled possibilities for revolutionizing digital governance. Future research should prioritize the scalability of these technologies, the establishment of new governance frameworks, and the ethical implications of artificial intelligence on public decision-making. Through the identification and resolution of acknowledged obstacles and the use of technological advantages, governments may construct governance systems that are more effective, open, and responsible. This study provides a basis for policymakers and experts to explore advanced digital governance solutions.